Analysis of Commercial Bank Performance Dynamics Based on KBMI1–KBMI4 Using a Panel ECM Approach - Tri Basuki, Agus (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the performance dynamics of commercial banks in Indonesia based on KBMI1, KBMI2, KBMI3, and KBMI4 groups using a dynamic panel Error Correction Model (ECM) approach. The data used consist of monthly panel data covering the period from June 2025 to January 2026. The ECM model is employed to examine both short-term and long-term relationships among variables affecting bank performance, while also capturing the adjustment process toward long-run equilibrium. The results indicate that there is a long-run equilibrium relationship between the variables studied and bank performance across all KBMI groups. The Error Correction Term (ECT), which is significant and negatively signed, suggests that when short-term disequilibrium occurs, the system will adjust back toward long-term equilibrium. This finding implies that the model used is appropriate in capturing the adjustment dynamics of banking performance. In the short run, several variables exhibit varying effects on bank performance across KBMI groups. These differences in responses reflect heterogeneity in behavior among bank groups, where banks in higher KBMI categories tend to demonstrate greater stability compared to those in lower KBMI groups. Furthermore, the estimation results show that the dynamic panel model with the ECM approach is capable of explaining variations in bank performance reasonably well, making it relevant for analyzing the banking sector. Overall, this study concludes that the performance of commercial banks in Indonesia is influenced not only by short-term factors but also significantly determined by long-term equilibrium relationships. The ECM approach proves to be effective in capturing these dynamics, particularly in distinguishing characteristics across KBMI groups.